Quantum Based Private Chat Space for Secure Organization - Mrs. J. Prabavadhi,; Amirtha Varshhini. S,; Bhuvaneshwari. S,; Priyadarshini. R,; Yuavsri. M, (The Bioscan, 2026)
The project "Quantum-Based Private Chatspace for Secure Organization" focuses on developing a secure communication platform tailored for organizational use. Leveraging quantum communication technologies, it aims to establish a chat environment capable of protecting sensitive information. The system will utilize quantum key distribution (QKD) to create and exchange cryptographic keys that are inherently resistant to eavesdropping, laying a solid foundation for secure communication. Key features will include end-to-end encryption, message integrity checks, and user authentication to meet enterprise-level security demands. The implementation of quantum security protocols will greatly strengthen data privacy and confidentiality, offering a cutting-edge defense against modern cyber threats. Furthermore, the project will involve a detailed assessment of potential security risks and rigorous testing to validate the system’s reliability and real-world applicability, thereby promoting advanced communication solutions in organizational settings.